Oral 3.03: Increasing number of thymectomies performed in the United States - Kim, Jae (J Thorac Dis, 2015)
BACKGROUND: Thymoma is a relatively rare disorder, but the true incidence in the United States is unknown because only cases described as “malignant” or “invasive” on final pathology reports are included in cancer registry data. An increasing number of thymomas may be identified incidentally on CT scans done for other purposes. As minimally invasive techniques have become more prevalent, thymectomy may also be offered for more patients. For these reasons, we hypothesized that the use of thymectomy has increased in the U.S. in recent years. METHODS: Using the Nationwide Inpatient Sample (NIS) from 1998 to 2011, we identified 6,457 patients who underwent thymectomy as a primary procedure. We also used the Surveillance, Epidemiology and End Results (SEER) database to identify the incidence of malignant thymoma from 1998 to 2011. Ordinary least squares regression was performed to assess trends in the incidence of thymectomy and malignant thymoma. RESULTS: From 1998 to 2011, the incidence of thymectomy per 100,000 admissions increased from 4.4 to 6.6 with annual increase of 3.6% (P=0.002). A total of 2,132 cases of malignant thymoma were reported in SEER from 1998 to 2011. There was not an increase in the incidence of malignant thymoma (P=0.14). From 2009 to 2011, 22% (n=362) of thymectomies were performed thoracoscopically and 9.1% were performed robotically (n=146). CONCLUSIONS: The number of thymectomies performed in the U.S. has increased in recent years. This does not appear to correspond to a definite increase in the incidence of malignant thymoma. It is unclear whether the true incidence of thymoma is increasing or whether thymectomy is simply becoming more common. This data demonstrates the need for more comprehensive reporting of thymomas and we advocate inclusion of all thymomas in cancer registry data.